2017
DOI: 10.1248/cpb.c16-00514
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Meloxicam and Meloxicam Metabolites in Rat Plasma Using a High-Performance Liquid Chromatography-Ultraviolet Spectrophotometry Method

Abstract: A high-performance liquid chromatography-ultraviolet spectrophotometry (HPLC-UV) method for the determination of meloxicam (MEL) and meloxicam metabolites (5′-hydroxy meloxicam (5-HMEL) and 5′-carboxy meloxicam (5-CMEL)) has been developed. After extraction of MEL, 5-HMEL, and 5-CMEL from rat plasma using Oasis HLB cartridges, the extracts were separated with a Luna C18 (2) 100 A column (5 µm, 4.6 150 mm, Phenomenex) using a mobile phase of 50 mM phosphate buffer (pH 2.15, solvent A) and acetonitrile (solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Method Validation Evaluation of the method was performed as follows applying the procedures previously reported. 13) The method was validated for selectivity, recovery, linearity, accuracy, and precision. The validation was conducted in accordance with the guidelines of the National Institute of Health Sciences (NIHS).…”
Section: Pretreatment Of Rat Plasma Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Method Validation Evaluation of the method was performed as follows applying the procedures previously reported. 13) The method was validated for selectivity, recovery, linearity, accuracy, and precision. The validation was conducted in accordance with the guidelines of the National Institute of Health Sciences (NIHS).…”
Section: Pretreatment Of Rat Plasma Samplesmentioning
confidence: 99%
“…Among various PIs, GB1101 was regarded as the most promising drug. 6,7) MATERIALS AND METHODS Reagents and Solutions PI was synthesized by Nihon University School of Medicine following the method of Bando et al 12) The chemical structure of PI was shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, Meloxicam (MLC) is 4-hydroxy-2-methyl-N-(5methyl-2-thiazolyl)-2H-1,2-benzothiazine-3-carboxamide-1, 1-dioxide ( Fig. 1a) [1], a new nonsteroidal anti-inflammatory drug (NSAID) derived from enolic acid, which exhibits cyclooxygenase (COX)-2 selectivity over COX-1 as described in a randomized double-blind study [2]. Meloxicam is used in the treatment of rheumatoid arthritis, osteoarthritis, and other joint diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Plentiful UV-VIS, HPLC, HPLC-MS/MS, LC-MS, LC-MS-MS, LC-ESI-MS/MS, LC-MS/TOF, and LC-MS analytical methods have been documented for quantifying the MLC from different formulation either alone or in combination with pharmacotherapeutic agents in biological fluid [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]; a couple of them namely were employed liquid-liquid extraction or protein precipitation extraction (PPE) approach for quantification of MLC from biological sample [5,7,14]. In spite of that, the reported approaches are time-consuming; some of them used organic solvents and hazardous solvents for the extraction process, and some of which reported much less recovery which may be due to the drug loss during the transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The repeatability of HPLC analyses is generally expressed as the relative standard deviation (RSD) of peak area and/or peak height measurements. [1][2][3][4][5] As a single chromatogram normally requires more than 10 min to generate, statistical repeatability assessments based on multiple measurements involve substantial quantities of chemical samples and experimental time.…”
Section: Introductionmentioning
confidence: 99%